1989
DOI: 10.1111/j.1530-0277.1989.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Recovery in Alcoholics

Abstract: A cross-sectional study of alcoholics who varied widely in duration of abstinence was combined with a four-year follow-up study of the same subjects. Together, the data demonstrated a course of recovery in abstinent alcoholics measured in three ways: severity of symptoms, probability of relapse, and work history. Additionally, the subjects showed high rates of smoking cessation. By every measure, the course of recovery seemed essentially the same in men and women. The recovery process was most rapid in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 22 publications
2
49
0
1
Order By: Relevance
“…This has important implications for relapse in human alcoholics as it suggests that violations of abstinence during the early withdrawal phase may increase the magnitude of subsequent lapses. Certainly, in human studies there is strong evidence that the longer a recovering alcoholic can stay abstinent, the lower the chance for relapse (De Soto et al 1989). This may primarily be due to the recovery from the protracted withdrawal syndrome and repair of social and occupational The three pre-vapor test sessions were used for group selection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has important implications for relapse in human alcoholics as it suggests that violations of abstinence during the early withdrawal phase may increase the magnitude of subsequent lapses. Certainly, in human studies there is strong evidence that the longer a recovering alcoholic can stay abstinent, the lower the chance for relapse (De Soto et al 1989). This may primarily be due to the recovery from the protracted withdrawal syndrome and repair of social and occupational The three pre-vapor test sessions were used for group selection.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, it was shown that distress-related symptoms correlated with relapse in alcoholics who were abstinent for less than two years (De Soto et al 1989). The more pro- Received March 2, 1999; revised August 25, 1999; accepted December 6, 1999.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The independent control over line crossings and social interaction behavior due to experimental manipulations (File 1980;Overstreet et al 2002) and pharmacological challenges (this study) suggest that independent neural mechanisms may be involved in the affective and physical withdrawal signs in alcoholics (De Soto et al 1989;Miller and Harris 2000). Because the drugs used in this study preferentially counteracted the affective symptom (anxiety-like behavior), and because affective symptoms are important risks to relapse in alcoholics (Curran et al 2000;Strowig 2000;Driessen et al 2001), it is possible that the agents that counteracted the social interaction deficits in the rats may reduce relapse in alcoholics.…”
Section: Discussionmentioning
confidence: 99%
“…He found that both groups were more likely to get sober through AA than with any professional treatment available at that time (28). Similarly, reduced symptoms, better work, and family history were found in examining long-term outcome of a sample of AA members (29). Of interest, both professional treatment and AA participation were each associated with an improved clinical outcome, but a better outcome was observed when patients experienced both treatment and AA participation (30).…”
Section: Two Culturesmentioning
confidence: 99%